2020
DOI: 10.25234/pv/8089
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Environmental Accounting and Reporting: The Case of Croatian Listed Manufacturing Companies

Abstract: The importance of environmental accounting has been recognised on a global scale, and thus environmental reporting has become legally required. The implementation of environmental accounting results in environmental information that has become part of the company's non-financial report, as well as a component in creating a comprehensive overview of the company's business activities. The aim of this paper is to research into the environmental accounting and reporting within Croatian listed manufacturing compani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…To answer the research questions, this paper presents the content and nature of publicly available non-financial information in the Croatian hospitality industry and provides comments to suggest improvements in content and make it clearer and more understandable for stakeholders. The content and type of non-financial information were selected based on the methodology used in previous research [56][57][58] which was additionally developed with the category and variables related to the requirements of the EU Directive.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To answer the research questions, this paper presents the content and nature of publicly available non-financial information in the Croatian hospitality industry and provides comments to suggest improvements in content and make it clearer and more understandable for stakeholders. The content and type of non-financial information were selected based on the methodology used in previous research [56][57][58] which was additionally developed with the category and variables related to the requirements of the EU Directive.…”
Section: Methodsmentioning
confidence: 99%
“…In answering the research questions, non-financial information was examined following previous research [56][57][58] and codes were given as follows: 0 if the information is not available (missing), 1 if the information is only mentioned, 2 if information is described, 3 if information is available in units of measurement.…”
Section: Methodsmentioning
confidence: 99%
“…This study also explained that sustainability practices are ordered to enhance the firm reputation and organizational commitment. Some authors have also suggested that environmental reporting has become a constituent part in the non-financial reporting into the company's all-inclusive businesses (Zrnić et al, 2020).…”
Section: Environmental Accounting Practicesmentioning
confidence: 99%
“…The main purpose of green accounting in companies is reflected in the possibilities of better planning and better business decision-making. Namely, green accounting is primarily internally oriented and generates environmental information "to help management make decisions referring to prices, cost control, capital budgeting, and external use, thus revealing information about the environment that is of interest to the public and the financial community" (Zrnić et al, 2020, p. 49, quoted from Yakhou & Dorweiler, 2004. According to Rewadikar (2014), the benefits of implementing green accounting within an economic entity are: 1) provision of useful information regarding decision making for level and structure of production, value of investment and environmental costs;…”
Section: Figure 12 the Subsets Of Green (Environmental) Accountingmentioning
confidence: 99%